La “perspectiva relacional” y el “enfoque de redes” en el análisis de los movimientos sociales. Aproximaciones preliminares a un estudio de caso - Jaramillo-Marín, Jefferson (Prospectiva. Revista de Trabajo Social e Intervención Social, 2009)
The relational perspective and networks approach offers a novel platform in the sociological analysis of relationships and transactions that take place in several scenarios of social life. This article describes some of the theoretical contributions that provide both, as well as its analytical potential in terms of understanding social movements. Returning some postulates of networks approach, to highlight in a preliminary way, how the National Movement of Victims of State Crimes in Colombia (MOVICE) can be understood under the logic of a heterogeneous and dynamic network of relationships and actions of resistance and political mobilization counter hegemonic. While his flag fight is against state impunity, specifically for a significant sector of Colombian victims of historical conflict, can also be considered an example of national defense network that increasingly covers more social and political demands, and builds a subaltern struggle by the radicalization of a more inclusive democratic project in Colombia.